Relação dos nomes em a Hora da Estrela, de Clarice Lispector, com o 1 Macabeus: uma análise através dos jogos fônicos, metáforas e anagramas da linguística estrutural. - Melo, Robson Anselmo Tavares de (2021)
In this thesis, linguistics, literature and theology are intertwined in order to investigate the relations of names in The Hour of the Star, by Clarice Lispector, with 1 Maccabees. The last work published by the author, it is one of the most intriguing and investigated texts in national literature not only because it was written in a long and painful moment of her life. But, also, for coadunating in its composition both existential and linguistic reflections. The latter are due to the fact that the words in it connotes much more than what is simply said. This junction is at the core of our investigative interest, which proposes to research, based on Saussurian and Jacobsian structural linguistics, names that emerge from others - from the title and the named and unnamed characters - in Clarice's respective work, which are related to the biblical book 1 Maccabees - a theological element. Regarding Ferdinand de Saussure's studies, we use the foundations of his research on sound games3, associative relations and anagrams - the latter in an illustrative way, but that converge with the phonic games in relation to homophony/anaphony -; as for Roman Jakobson's, we use the metaphorical processes (similarity) developed from the associative axes - in absentia - of Saussure. Moreover, the thematic existential relations in the author's work are present not only in the reflections proposed around the Being, but also by the influence of her own religious background, which provided her with knowledge of the respective sacred text, influencing the construction of the respective literary fiction. Thus, through the selected theoretical contributions, we seek to find in the names in the work, respectively: the dissemination of phonic elements - games and anagrams (illustratively) - by the substitution (similarity) - metaphorical macabre evidences. We stress that, metologically, all the names in the work were analyzed either by the sound-related or the metaphorical contributions. We emphasize that the metaphorical contribution was employed to those that, in a generic way, are related to the sacred text. In synthesis, our investigation proposes, based on structural linguistic studies in a work of the national literary collection, to find names that are not present, but that influenced its fictional texture.